A brief analysis of the concentration of Bitcoin mining power - Llases, Luis (Papeles de Europa, 2021)
Bitcoin is a decentralized computer network that allows the sending of value among its users. For this, an interchangeable and fractionable account unit called bitcoin is used. The main characteristic of this system is that it does not need a central unit to administer it, it works through an incentive system that ensures that a series of users called miners act in such a way that transactions can be carried out safely. Basically, these miners compete with each other to add new transactions to the ledger, for which they must solve a mathematical problem established by the system. To do so, they must consume some resources (computer hardware, electricity, etc.) with which they generate a processing power to solve the mathematical problem. As payment for the expense that the miners make, they receive a reward in the form of new mined bitcoins and users’ commissions. It is a necessary condition for the network to be secure that the mining activity remains decentralized. However, recent years have seen an increase in the concentration of processing power. Given the importance of this issue for cryptocurrency, this work has tried to understand what the reasons for the concentration have been and if they can be considered as trends that will continue to operate in the long term. The study concludes that the reduction in miners’ rewards and economies of scale have been the main causes of concentration and that at least the first of these causes will continue to operate in the long term.